Medi8or: faculty of pharmacy, UiTM Penang shines at KIK convention 2025 (northern zone) - Ibrahim, Nurul Alyaa (Faculty of Pharmacy, 2025)
On 12 September 2025, the Medi8or team from the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Penang, achieved remarkable success at the UiTM KIK Convention 2025 (Northern Zone). The team comprised eight members: three academic staff and five supporting staff, including pharmacists and assistant pharmacists.